HOLOCENE SILICEOUS SEDIMENTS IN THE SEA OF OKHOTSK - Volokhin Yu.G.; Astakhov A.S.; Vashchenkova N.G. (My University, 2004)
The mineral and chemical compositions and physical properties of diatomaceous clayey–siliceous sediments in the Sea of Okhotsk are studied. Absolute masses of silica accumulation are determined. Their compositional model based on the silica content is similar to that of Late Jurassic and Olenekian–middle Anisian cherts of the Sikhote Alin region. The thickness of the Holocene siliceous unit and the absolute mass of siliceous deposits depended on bioproductivity in the upper water column and the seafloor topography. Absolute masses of SiO2 am (0.05–5.7 g cm–2 ka–1) and SiO2 fr (0.5–11.6 g cm–2 ka–1) are minimal on seamounts and maximal in depressions near foothills. These values match absolute masses of SiO2 fr accumulations in Triassic and Late Jurassic basins of the Sikhote Alin region (0.33–3 g cm–2 ka–1). Comparison of the composition and absolute masses of silica shows that Triassic and Late Jurassic siliceous sequences of Sikhote Alin could be accumulated in the marginal marine basin near a continent.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен